Developing Insights in Cartilage Repair - Emans, Pieter J.; Peterson, Lars (Springer London : Imprint: Springer, 2014)
This book reviews the current basic and clinical research into the mechanisms of cartilage injury and  its management. It illustrates the considerable progress made in the search for solutions to cartilage related problems.   Developing Insights in Cartilage Repair describes fundamental research and the use of biomaterials, bioreactors, and imaging as part of existing cartilage repair strategies, while revealing the on-going trends for emerging techniques. The aim of the Editors and their team of authorities in cartilage medicine has been to provide a link between laboratory work and the daily treatment of patients in a clinical setting. This book reveals the highly multidisciplinary nature of the topic and it will thus not only be of considerable interest to a large proportion of the orthopaedic community, but also any discipline in which cartilaginous tissue is involved, including otorhinolaryngology and plastic surgery. ·         Provides an insight of cartilage and its repair to physicians and scientists with an active interest in cartilage repair and new transplantation techniques ·         Describes different strategies to repair cartilage defects as well as fundamental research concerning cartilage biology and imaging ·         Up-to-date research enables fast clinical implementation of novel findings to optimize cartilage repair.